Direct observation of a fast single-crystal-to-single-crystal transformation from a CuII-framework to a CuI-chain mediated by ascorbic acid. Issue 11 (18th February 2016) - Song, Yang; Fan, Rui-Qing; Wang, Xin-Ming; Gao, Song; Du, Xi; Wang, Ping; Yang, Yu-Lin
Abstract : This research presents an exceedingly rare example of a visible single-crystal-to-single-crystal transformation from a 3D Cu II -framework to a 1D Cu I -chain under mild conditions and their tunable luminescence. Abstract : With the help of ascorbic acid as reductant, an exceedingly rare example of a visible single-crystal-to-single-crystal transformation from a Cu II -framework to a Cu I -chain under mild conditions has been observed, which involves the metal valence tautomerism and restructuring of bonds. The two compounds exhibit the properties of solvatochromism and luminescence aggregation-induced-emission towards CH3 OH, respectively.